Encapsulamento anafórico : um fenômeno linguístico textual constituído na relação sintático-semântica - Caierão, Janaina Rigo (2012)
This study is intended to present an analysis on encapsulating anaphor as a cohesive resource which mobilizes both the lexical choices and combinations to build the meaning of a text. This will be presented on the basis of two perspectives: in the light of syntagmatic and associative relations presented in General Linguistic Course (GLC) and also based on Textual Language studies. This word has noted that the occurrence of anaphoric encapsulating in three different chronic from different newspapers in RS state. We have taken Ferdinand de Saussure, Simon Bouquet, Ingedore Villaça Kock and Monica Magalhaes Cavalcante as main authors for this study. The research demonstrates that encapsulating anaphor is an important cohesive resource for referral and text organization, for it is able to demonstrate both associative and syntagmatic relations in a text tessitura, which allows the building of its sense. As the identification of this encapsulating anaphor was made, mainly formed by nominal expression, in each selected chronic, we have verified its performance in the corpus in question and proceeded to its analysis, taking previously established criteria in the methodological procedures into account. Based on this, we have noted that lexical choices and combinations, syntactic constructions and encapsulating anaphors are fundamentally necessary toward each other, in order to build the cohesion of a text and, in turn, its sense, highlighting the possible relationships which can be established between language units